Advanced Boundary Conditions for the Simulation of Fire Engulfment Tests of Cryogenic Storage Tanks - Alice Schiaroli; Giordano Emrys Scarponi; Christian Mata; Federico Ustolin; Valerio Cozzani (Chemical Engineering Transactions)
The fire engulfment of a cryogenic storage tank can be simulated using mathematical models. Currently, the available approaches reproduce the real case scenario considering a static full engulfment of the component. Unfortunately, given the dynamic nature of the fire, this simplification is often far from reality, primarily for fires in open environments where wind strongly affects the flame distribution on the tank surface. This study applies a digital image processing technique to replicate the time-varying partial engulfment of a cryogenic storage tank tested in external fire conditions. The obtained results are used to define dynamic boundary conditions implemented in a lumped model to estimate the pressurization and heating of the component during the fire attack. The study highlights the improved accuracy in the characterization of the fire obtainable with the present approach and emphasizes the need for a precise characterization of the system to correctly replicate the experimental data.